Social Control Model in Social Networking Site Communities - Meri Ani Saragih (Journal of Information Systems and Management (JISMA), 2023)
The presence of social networking sites (SJS) has given rise to a new phenomenon in the use of information technology in a social context. The human culture that exists in the real world has now extended to SJS, not only the positive but also the negative, including pornography and racism. This paper proposes a conceptual model of social control so that forms of negative and deviant culture can be reduced in the SJS community. The model proposes that social control can be carried out at two layers, namely the social interaction layer and the SJS technology layer. There are three factors—moral trust, attachment, and commitment and engagement—at the social interaction layer that, when strengthened, can reduce deviance. At the technology layer, there are two components—persuasive technology and coercive technology—that SJS can leverage to reduce bias.